Konsep Matematika Dalam Proses Pembuatan Besek - Setyadi, Danang (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
Producing processes of besek are indicated to be strongly related to several concepts of mathematics. This research has a purpose to obtain detailed information about it. The da-ta was obtained by doing interview with three respondents who have vast experience in making besek. Results of the research shows there are three concepts of mathematics re-lated to producing processes of besek, namely estimation, patterns, and geometry. Esti-mation in besek producing processes consists of measuring and numeration estimation. Patterns are found the stage in making benikan, ngiseni, and ngembakke, while geometry concept found is related to tessellation, symmetry, and relation of lines.